University entrance language tests: A matter of justice. (October 2018) - Deygers, Bart; Van den Branden, Kris; Van Gorp, Koen
University entrance language tests are often administered under the assumption that even if language proficiency does not determine academic success, a certain proficiency level is still required. Nevertheless, little research has focused on how well L2 students cope with the linguistic demands of their studies in the first months after passing an entrance test. Even fewer studies have taken a longitudinal perspective. Set in Flanders, Belgium, this study examines the opinions and experiences of 24 university staff members and 31 international L2 students, of whom 20 were tracked longitudinally. Attention is also given to test/retest results, academic score sheets, and class recordings. To investigate the validity of inferences made on the basis of L2 students' scores, Kane's (2013) Interpretation/Use Argument approach is adopted, and principles from political philosophy are applied to investigate whether a policy that discriminates among students based on language test results can be considered just. It is concluded that the receptive language requirements of university studies exceed the expected B2 level and that the Flemish entrance tests include language tasks that are of little importance for first-year students. Furthermore, some of the students who failed the entrance test actually managed quite well in their studies – a result that entails broad implications concerning validation and justice even outside the study's localized setting.